Thailand : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report, 2022)
Thailand's economy is recovering from an unprecedented crisis emanating from multiple waves of the COVID-19 pandemic. Ample policy space has allowed a swift and bold policy response and vaccine rollout has accelerated. However, the recovery is weak and uneven across sectors, with inflation rapidly rising driven by energy prices. Downside risks dominate the outlook, sharpening policy tradeoffs. The pandemic has also brought to the fore the urgency for Thailand to identify new growth drivers to reverse the pre-pandemic trend of declining productivity growth and meet the challenges of the post-pandemic world.